E-books como elementos de innovación y gestión del conocimiento Las posibilidades comunicativas de los libros electrónicos (2016)
The book was one of media products, which enabled the democratization of access to information. With the e-book we are witnessing a revolution in the digital world. If the media, social participation, media convergence processes have been vital in shaping the vast Internet network, turn now is for the publishing industry with the arrival and the offer in the market of electronic publishing.